Pembinaan Penyusunan Laporan Keuangan pada Usaha Jahit Rumahan - Neni Marlina Br Purba; Sri Zetli; Handra Tipa (Pusat P2M Politeknik Negeri Batam, 2021)
Apart from being good at sewing, sewing businesses also need to understand good financial management and governance so that the business runs smoothly. It is not uncommon for business actors to still find it difficult to understand how to make financial reports properly, because they think that financial reports are not too important for their businesses, especially middle-to-lower businesses such as home sewing businesses. Based on these problems, the aim of this dedication is the Development of Financial Statements for Home Sewing Businesses. The method used is the preparation of financial statements starting from the preparation of balance sheets, income statements, reports of changes in capital, cash flow reports and reports on financial statements that are carried out directly. In addition, the service team also provides techniques on how to sit and design work for tailors so that workers feel comfortable and stay healthy while carrying out their work. Based on the coaching that has been given for 5 meetings, it is concluded that the participants are very interested and enthusiastic and can follow and understand the whole series of coaching that has been carried out until its completion. This was proven by the participants who were able to make their own sewing business financial reports. This guidance is very important, especially for business actors in order to know all business activities for future evaluation.